Tooth defects of EEC and AEC syndrome caused by heterozygous TP63 mutations in three Chinese families and genotype‐phenotype correlation analyses of TP63‐related disorders - Jinglei Zheng (Molecular Genetics & Genomic Medicine, 2019)
Abstract Background Ectrodactyly‐Ectodermal dysplasia‐Cleft lip/palate (EEC) syndrome and Ankyloblepharon‐Ectodermal defects‐Cleft lip/palate (AEC) syndrome belong to p63 syndromes, a group of rare disorders exhibiting a wide variety of clinical manifestations. TP63 mutations have been reported to be associated with both EEC and AEC. Methods Analysis of whole exome sequencing (WES) from patients with EEC or AEC syndrome and Sanger sequencing from family members. Results We confirmed that three Chinese pedigrees affected with EEC or AEC harboring a distinct TP63 mutation, and described novel clinical phenotypes of EEC and AEC, including the presence of cubitus valgus deformity and taurodontism, which were discordant to their classical disease features. We also analyzed the genotype–phenotype correlation based on our findings. Conclusion We reported that the cubitus valgus deformity in patients with EEC and severe taurodontism in a patient with AEC had not been mentioned previously. Our study expands the phenotypic spectrum of EEC and AEC syndrome.